EPV 10. Bi-frontal transcranial direct current stimulation does not modulate sleep continuity in patients with insomnia. Issue 9 (September 2016) - Frase, L.; Piosczyk, H.; Selhausen, P.; Zittel, S.; Jahn, F.; Krone, L.; Feige, B.; Maier, J.G.; Riemann, D.; Nitsche, M.A.; Nissen, C.
Abstract : Objective and background: The most influential neurobiological model of insomnia disorder is the 'hyperaorusal model', which states increased level of arousal during day and nighttime as a fundamental characteristic of the disorder (Riemann et al., 2010 ). Prior work emphasizes the crucial role of cortical activity levels and cortico-thalamic feedback in this disorder (Nofzinger et al., 2004 ). In a prior study, our research group demonstrated that bi-frontal anodal tDCS significantly decreased total sleep time (TST) and increased cortical arousal during wakefulness as indexed by resting state EEG gamma power in healthy participants (Frase et al., 0000 ). To further elucidate the relevance of prefrontal activity levels in insomnia disorder, we tested the hypothesis that bi-frontal cathodal tDCS results in an increase of TST by reducing cortical hyperarpousal in patients with insomnia with anodal tDCS inducing reverse effects. Methods: Nineteen patients with nonorganic insomnia (13 females, 6 males, age 43.8 ± 15.1 years, 20–60 years) were included in the analysis. After adaptation to the sleep laboratory conditions, each participant underwent a baseline and three experimental nights in intervals of 3–7 days with a tDCS protocol immediately prior to polysomnography (11 pm to 7 am) according to standard procedures. The polysomnographic parameter total sleep time (TST) was defined as the main outcome parameter for of sleep continuity. Three different conditions (activation, deactivation, sham) were applied in a counterbalanced order. tDCS was delivered by a battery-driven, micro-processor-controlled constant current stimulator (Neuro-conn, Illmenau, Germany) and transferred by two pairs of electrodes (5 cm × 7 cm and 10 cm × 10 cm) covered with electrode cream positioned over FP1/FP2, respectively over P3/P4. A current of 1 mA was applied over each target electrode with a ramp up/ramp down of 30 s at the start and end of each stimulation and an interstimulusinterval (ISI) of 20 min. Results: In contrast to our hypothesis, bi-frontal tDCS did not result in significant changes in sleep continuity or architecture. Analyses of subjective sleep ratings detected no differences between conditions (Repeated measures ANOVAs conducted for all three conditions separately, all p  > 0.6). Discussion: In contrast to our findings in healthy participants, the current results in patients with insomnia do not show differences in sleep continuity after tDCS. Instead, the sleep pattern in insomnia patients appears to be robust to cortical stimulation, which could be caused by persistant hyperarousal overriding possible tDCS-effects.